Coryneform bacteria isolated from middle ear fluid. - Simonet, M (1993)
Nineteen strains of facultatively anaerobic gram-positive rods isolated in pure culture from middle ear fluids were identified. All effusions were collected by tympanocentesis in children with acute otitis media. Identification of microorganisms to the genus level was done by studying the cell wall composition. Sixteen strains contain meso-diaminopimelic acid and arabinogalactan polymer but lack mycolic acids; therefore, these strains do not belong to a previously described taxon. Because of similarities with Corynebacterium afermentans (Centers for Disease Control group ANF-1), we temporarily classified these mycolateless strains ANF-1 like. Isolation of these microorganisms in pure culture from middle ear fluids collected by tympanocentesis is a strong argument for their involvement in acute otitis media.